Advancements in corrected Euler–Maclaurin-type inequalities via conformable fractional integrals - Yaren Acar; Hüseyin Budak; Umut Bas; Fatih Hezenci; Hüseyin Yıldırım (Boundary Value Problems)
Abstract In this research article, equality is proved to obtain corrected Euler–Maclaurin-type inequalities. Using this identity, we establish several corrected Euler–Maclaurin-type inequalities for the case of differentiable convex functions by means of conformable fractional integrals. Moreover, some corrected Euler–Maclaurin-type inequalities are given for bounded functions by fractional integrals. Additionally, fractional corrected Euler–Maclaurin-type inequalities are constructed for Lipschitzian functions. Finally, corrected Euler–Maclaurin-type inequalities are considered by fractional integrals of bounded variation.